Evaluation of the Lecturers' and Students' Views about Coursebook Classes at Yildiz Technical University, School of Foreign Languages, Basic English Department - Akpur, Ugur; Altun, Sertel (NESIBE AYDIN EDUCATION INST, 2012)
The aim of this study is to evaluate prep class students' and lecturers' views on Coursebook classes at Yildiz Technical University, School of Foreign Languages, Basic English Department using Delphi Technique. The study group consisted of 27 lecturers who were teaching Coursebook classes in prep classes and 36 students in the academic year 2011-2012. Data were collected in two rounds of Delphi Technique. In the first Delphi questionnaire, participants were given a questionnaire including open-ended questions. Using the data gained from the first Delphi questionnaire, the second Delphi questionnaire was developed and given to the participants. The data gained from the second questionnaire were analyzed through frequency and percentage. The findings indicated that lecturers and students generally had negative ideas about Coursebook Classes at prep school.
Keywords: Curriculum evaluation; delphi technique; foreign languages; coursebook; Education & Educational Research